Application of difunctional additive in aqueous zinc ion battery

By using methionine (MET) as a dual-function electrolyte additive in aqueous zinc ion batteries, the stability problems of zinc negative electrode and vanadium-based positive electrode are solved, and the cycle stability and capacity retention rate of the battery are significantly improved.

CN119481056APending Publication Date: 2025-02-18FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411463141.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Water-based zinc ion batteries (AZIBs) face problems such as hydrogen evolution, corrosion, severe dendrite growth and structural collapse and dissolution of vanadium-based positive electrode materials, resulting in serious failure of the battery and difficulty in achieving deep charging and discharge.

Method used

Methionine (MET) is used as a dual-function electrolyte additive. By regulating the solvation structure of the electrolyte, it inhibits water activity, reduces HER and other related parasitic reactions, regulates Zn2+ flux, promotes orderly Zn deposition, and is on vanadium-based The CEI film containing products such as ZnF2 is formed in situ on the surface of the positive electrode, which inhibits the failure of the vanadium-based positive electrode.

Benefits of technology

The stability of the vanadium-based positive electrode and the stable deposition of the zinc negative electrode were significantly improved, the cycle stability of the K2V8O21||Zn whole battery was improved, and the capacity retention rate was increased from 10.2% to 99.8%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481056A_ABST
    Figure CN119481056A_ABST
Patent Text Reader

Abstract

The invention discloses an application of a difunctional additive in an aqueous zinc ion battery. The aqueous zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte, the positive electrode comprises a vanadium-based material and methionine; and the negative electrode is a Zn negative electrode. The electrolyte comprises a zinc salt aqueous solution and methionine. The methionine (MET) is used as a difunctional AZIBs additive, protects the vanadium-based positive electrode, inhibits the failure of the vanadium-based positive electrode material, induces the uniform deposition of the zinc negative electrode, and improves the cycling stability of the zinc ion battery. Compared with a bare electrolyte, the capacity retention ratio of the KVOZn total battery added with the MET after 800 cycles under the low current density of 1A g <-1 > is greatly improved to 99.8% from 10.2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the application of bifunctional additives in aqueous zinc ion batteries, belonging to the field of batteries. Background Art

[0002] Aqueous zinc-ion batteries (AZIBs) have a high capacity (5851 mA h cm -3 , 820mA hg -1 ), low redox potential (-0.76V vs SHE), high abundance and low cost, etc., have attracted great attention in the field of energy storage. However, AZIBs face a series of problems, including but not limited to hydrogen evolution, corrosion, severe dendrite growth of zinc anode, and structural collapse and dissolution of positive electrode materials. The above problems will lead to serious failure of AZIBs, making it difficult to achieve deep charge and discharge process of the battery, which hinders the practical application of AZIBs.

[0003] In response to the problems of AZIBs zinc negative electrode, the common solutions currently include electrolyte optimization and modification, surface coating, interface design and structural optimization strategies, etc. Among them, the most convenient and effective is the optimization and modification of the electrolyte, which is achieved by adding electrolyte additives with specific functionality to achieve the regulation of the zinc negative electrode. Organic small molecule additives have attracted the attention of researchers because of their relatively simple structure, diverse functions, and wide sources. In terms of AZIBs positive electrode, vanadium-based materials are excellent aqueous battery positive electrode materials because of their large lattice structure, variable valence states, facilitating ion shuttling, and providing high specific capacity. However, due to the co-embedding of water and zinc ions in AZIBs, vanadium-based positive electrode materials will cause large lattice changes after multiple cycles, which limits the structural stability of vanadium-based materials and poses the risk of structural collapse and dissolution, so they also face difficulties in practical applications. Summary of the invention

[0004] In view of the problems faced by aqueous zinc-ion batteries, such as Zn negative electrode dendrite growth and interface reaction, and vanadium-based positive electrode structure collapse. The functional interface layer on the positive electrode surface and the high-concentration salt electrolyte can play a certain role in inhibiting the failure of vanadium-based positive electrode materials. This application proposes a bifunctional electrolyte additive methionine (MET), which has a unique role in inducing uniform deposition of zinc negative electrodes and inhibiting the failure of vanadium-based positive electrode materials.

[0005] MET affects the solvation structure of the electrolyte, inhibits water activity, and thus reduces HER and other related parasitic reactions. 2+ Flux, improve Zn 2+The deposition dynamics on the zinc negative electrode side induces the preferential growth of the Zn(101) crystal plane, thereby promoting ordered Zn deposition. In particular, MET can in situ generate a CEI film containing products such as ZnF2 on the surface of the vanadium-based cathode to inhibit the failure of the vanadium-based cathode, while regulating the surface electronic state and Zn 2+ diffusion behavior, which can reduce Zn 2+ The intercalation process destroys the structure of the vanadium-based cathode. Compared with the bare electrolyte, the K2V8O 21 ||Zn full battery at 1Ag -1 After 800 cycles at low current density, the capacity retention rate increased significantly from 10.2% to 99.8%. Therefore, MET has considerable application prospects as a dual-functional additive that can improve the stability of vanadium-based positive electrodes and promote the stable deposition of zinc negative electrodes.

[0006] Application of methionine as a bifunctional additive in aqueous zinc ion batteries.

[0007] Optionally, the aqueous zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte;

[0008] The positive electrode includes a vanadium-based material and methionine;

[0009] The negative electrode is a Zn negative electrode.

[0010] Optionally, the usage ratio of methionine to vanadium-based material is 1:1.5 to 1:3.

[0011] Optionally, the usage ratio of methionine and vanadium-based material is 1:2.

[0012] Optionally, the vanadium-based material is selected from K2V8O 21 and / or V2O5.

[0013] Optionally, the electrolyte comprises an aqueous zinc salt solution and methionine.

[0014] Optionally, in the electrolyte, the amount of methionine used is 0.01 mol / L to 0.1 mol / L.

[0015] Optionally, the zinc salt aqueous solution is selected from a ZnOTF aqueous solution.

[0016] Optionally, the preparation method of the positive electrode includes: mixing vanadium-based material and methionine in water, stirring evenly, and drying to obtain an active material; mixing the active material, acetylene black and PVDF to prepare a slurry, evenly coating it on graphite paper, and drying to obtain the positive electrode.

[0017] Optionally, the method for preparing the electrolyte comprises: adding methionine to a zinc salt aqueous solution.

[0018] The beneficial effects of this application include:

[0019] The present application provides an application of methionine as a bifunctional additive in aqueous zinc ion batteries. Methionine (MET) is a bifunctional AZIBs additive that protects vanadium-based positive electrodes, inhibits the failure of vanadium-based positive electrode materials, induces uniform deposition of zinc negative electrodes, and improves the cycle stability of zinc ion batteries. Compared with the bare electrolyte, K2V8O 21 ||Zn full battery at 1A g -1 After 800 cycles at low current density, the capacity retention rate increased significantly from 10.2% to 99.8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The KVO@M||Zn battery of Example 1 and the KVO||Zn battery of Comparative Example 1 at 1A g -1 Comparison of cycling performance under different current densities.

[0021] Figure 2 The V2O5@M||Zn battery of Example 2 and the V2O5||Zn battery of Comparative Example 2 at 1A g -1 Comparison of cycling performance under different current densities.

[0022] Figure 3 Microscopic morphology of the deposition uniformity of the Zn negative electrode for the KVO||Zn battery assembled with the OTF-M10, OTF-M50, OTF-M100 electrolytes of Example 3 and the OTF electrolyte of Comparative Example 1.

[0023] Figure 4 This is a comparison chart of the cycle life of KVO||Zn full batteries assembled with the OTF-M10, OTF-M50, OTF-M100 electrolytes of Example 3 and the OTF electrolyte of Comparative Example 1.

[0024] Figure 5 This is a cycle life diagram of the Zn||Zn symmetric battery assembled with the OTF-M50 electrolyte of Example 4 and the OTF electrolyte of Comparative Example 3.

[0025] Figure 6 This is a cycle life diagram of the Zn||Cu symmetric battery assembled with the OTF-M50 electrolyte of Example 5 and the OTF electrolyte of Comparative Example 4. DETAILED DESCRIPTION

[0026] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0027] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0028] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0029] Material:

[0030] Zinc trifluoromethanesulfonate (Zn(CF3SO3)2, ZnOTF, 98%), methionine (C5H 11 O2NS, 99%) was purchased from MacLean.

[0031] Potassium chloride (KCl, ≥99.5) and potassium iodide (KI, ≥99%) were purchased from Sinopharm Group.

[0032] Vanadium pentoxide (V2O5 (99%)), zinc sulfate heptahydrate (ZNSO4·7H2O (AR)), and sodium dodecyl sulfate (SDS (≥97%)) were purchased from Aladdin.

[0033] Glass fiber membrane (GF) was purchased from Whatman Company.

[0034] PVDF (HSV 900) was purchased from Arkema.

[0035] Acetylene black (Kappa 100) was purchased from Cluder Corporation.

[0036] The rest are commercially available.

[0037] The analysis method in the examples of this application is as follows:

[0038] Material characterization methods:

[0039] The morphology of the samples was characterized by scanning electron microscopy (SEM, SU8010). The distribution and content of elements on the surface of the samples were analyzed by EDS. The crystal structure of the samples was obtained by X-ray diffractometer (XRD, Miniflex600, Cu Kα). The contact angle of different electrolytes on the surface of zinc foil was measured by contact angle tester (DSA25). The effect of additives on the functional groups in the electrolyte was analyzed by in situ laser confocal Raman spectrometer (LabRAM, Thermo Fisher Scientific). The Fourier transform infrared spectra of different electrolytes were recorded by infrared spectrometer (VERTEX70). X-ray photoelectron spectroscopy (XPS) was used to analyze the CEI composition on the surface of KVO electrode.

[0040] Battery testing method:

[0041] Cyclic voltammetry (CV) tests were performed on the Princeton electrochemical workstation for cathode||Zn batteries with a scan rate of 0.1 mV s-1 and a voltage range of 0.2 to 1.6 V. The CV tests for Zn||Cu and Zn||Ti were performed in the voltage range of -0.3 V to 0.2 V with a scan rate of 0.1 mV s-1. -1 . The acquisition range of electrochemical impedance spectroscopy (EIS) was between 100000 Hz and 0.1 Hz. Constant current charge and discharge tests and constant current intermittent titration technique (GITT) tests were carried out on the Newar test system. In the three-electrode system, zinc foil was used as the working electrode (W), platinum wire as the counter electrode (C), and Ag / Ag Cl as the reference electrode (R), and linear sweep voltammetry (LSV) and linear polarization curve tests were carried out in different electrolytes. The scan rate was 2 mV s-1, and the scanning potential range was -1.25 to -0.75 V. All batteries were assembled under open air conditions and aged for 6 hours before electrochemical testing.

[0042] Example 1

[0043] Preparation of potassium vanadate (K2V8O 21 (KVO)): 0.1818g vanadium pentoxide (V2O5) and 20ml deionized water, stir evenly to prepare solution A. 2.249g potassium iodide (KI) and 2.2365g potassium chloride (KCl) and 10ml deionized water, stir evenly to prepare solution B. Solution B is continuously added to 80℃ solution A, while keeping solution A in a stirring state, and then 0.1818g SDS is added to prepare solution C. Solution C is then kept in a 180℃ hydrothermal autoclave for 24h, centrifuged and dried to prepare potassium vanadate K2V8O 21 (KVO).

[0044] Preparation of KVO@M: 0.05 g methionine (MET) and 10 ml deionized water were stirred evenly, 0.1 g KVO was added, stirred for 12 h, and dried at 80 °C for 30 min to prepare KVO@M.

[0045] Preparation of electrode: Active material KVO@M, acetylene black and PVDF were mixed in a weight ratio of 7:2:1 to prepare slurry. Graphite paper was cut into a circle of Φ=14mm, and the prepared slurry was evenly coated on the graphite paper and dried in a forced air drying oven at 80℃ for 24h. The loading mass of active material per electrode was about 2mg / piece.

[0046] Electrolyte: Prepare 2 mol / L ZnOTF aqueous solution (referred to as OTF). 7.27 g zinc trifluoromethanesulfonate (ZnOTF) and 10 g deionized water were used to prepare a 2M ZnOTF aqueous solution (referred to as OTF), and 0.015 g MET (0.01 mol / L MET, referred to as OTF-M10), 0.075 g MET (0.05 mol / L MET, referred to as OTF-M50), and 0.15 g MET (0.1 mol / L MET, referred to as OTF-M100) were added respectively.

[0047] Battery assembly: KVO@M positive electrode, glass fiber separator and Zn negative electrode are stacked and assembled in sequence, and 2 mol / L ZnOTF aqueous solution is added and packaged into KVO@M||Zn battery.

[0048] Comparative Example 1

[0049] The operation is the same as that of Example 1, except that the KVO positive electrode, glass fiber separator and Zn negative electrode are stacked and assembled in sequence, 2 mol / L ZnOTF aqueous solution is added and packaged into a KVO||Zn battery.

[0050] Example 2

[0051] Different from Example 1, the V2O5@M positive electrode, glass fiber separator and Zn negative electrode are stacked and assembled in sequence, and a 2 mol / L ZnOTF aqueous solution is added and packaged into a V2O5@M||Zn battery.

[0052] Preparation of V2O5@M: 0.05 g MET and 10 ml deionized water were stirred evenly, 0.1 g unmodified V2O5 was added, stirred for 12 h, and dried at 80 °C for 30 min to prepare V2O5@M.

[0053] Comparative Example 2

[0054] The operation is the same as that of Example 2, except that the V2O5 positive electrode, glass fiber separator and Zn negative electrode are stacked and assembled in sequence, 2 mol / L ZnOTF aqueous solution is added and packaged into a V2O5||Zn battery.

[0055] Example 3

[0056] Electrode preparation: Active materials KVO, acetylene black and PVDF were mixed in a weight ratio of 7:2:1 to prepare slurry. Graphite paper was cut into a circle of Φ=14 mm, and the prepared slurry was evenly coated on the graphite paper and dried in a forced air drying oven at 80°C for 24 hours. The loading mass of active materials per electrode was about 2 mg / piece.

[0057] Electrolyte: Prepare 2 mol / L ZnOTF aqueous solution (referred to as OTF). 7.27 g zinc trifluoromethanesulfonate (ZnOTF) and 10 g deionized water were used to prepare a 2M ZnOTF aqueous solution (referred to as OTF), and 0.015 g MET (0.01 mol / L MET, referred to as OTF-M10), 0.075 g MET (0.05 mol / L MET, referred to as OTF-M50), and 0.15 g MET (0.1 mol / L MET, referred to as OTF-M100) were added respectively.

[0058] Battery assembly: KVO and Zn are used as electrodes and electrolyte to assemble into KVO||Zn battery.

[0059] The KVO positive electrode, glass fiber separator and Zn negative electrode were stacked and assembled in sequence, and OTF-M10, OTF-M50 and OTF-M100 electrolytes were added respectively and packaged into KVO||Zn batteries.

[0060] Example 4

[0061] The Zn positive electrode, glass fiber separator and Zn negative electrode are stacked and assembled in sequence, and OTF-M50 electrolyte is added and packaged into a Zn||Zn battery.

[0062] Comparative Example 3

[0063] The operation is the same as that of Example 4, except that the zinc Zn positive electrode, glass fiber separator and zinc Zn negative electrode are stacked and assembled in sequence, OTF electrolyte is added and packaged into a Zn||Zn battery.

[0064] Example 5

[0065] The copper Cu positive electrode, glass fiber separator and zinc Zn negative electrode are stacked and assembled in sequence, OTF-M50 electrolyte is added and packaged into a Zn||Cu battery.

[0066] Comparative Example 4

[0067] The operation is the same as that of Example 5, except that the copper Cu positive electrode, glass fiber separator and zinc Zn negative electrode are stacked and assembled in sequence, OTF electrolyte is added and packaged into a Zn||Cu battery.

[0068] Figure 1 The KVO@M||Zn battery of Example 1 and the KVO||Zn battery of Comparative Example 1 were prepared at 1Ag. -1 Comparison of cycling performance under different current densities. MET protects KVO to a certain extent. KVO@M||Zn full battery has a good cycling performance at 1A g -1 It can maintain stable cycling for more than 600 cycles at the current density. Therefore, MET can also effectively improve the stability of KVO electrode only as an electrode modification material.

[0069] Figure 2 The V2O5@M||Zn battery of Example 2 and the V2O5||Zn battery of Comparative Example 2 were prepared at 1Ag. -1 Comparison of cycling performance under current density. MET has a protective effect on V2O5 to a certain extent. V2O5@M||Zn full battery has a high current density of 1Ag. -1 It can maintain stable cycling for more than 500 cycles at the current density. Therefore, MET can also effectively improve the stability of V2O5 electrode only as an electrode modification material.

[0070] MET additive improves the surface flatness of zinc negative electrode

[0071] Using copper foil as the substrate, zinc was deposited on the surface of the copper foil using a double-electrode electrolytic cell (anode-consuming cathodic protection method) to further study the mechanism of the influence of MET additives on zinc deposition behavior. Figure 3 The KVO||Zn battery assembled with the OTF-M10, OTF-M50, and OTF-M100 electrolytes of Example 3 and the OTF electrolyte of Comparative Example 1, the microscopic morphology of the deposition uniformity of the Zn negative electrode, and the SEM image of the copper foil surface after electroplating with zinc. Figure 3 (a) OTF corresponds to the KVO||Zn battery assembled with the OTF electrolyte of Comparative Example 1, Figure 3 (b) OTF-M10, Figure 3 (c)OTF-M50, Figure 3 (d) OTF-M100 corresponds to the KVO||Zn battery assembled with OTF-M10, OTF-M50, and OTF-M100 electrolytes in Example 3. In the OTF system, the Zn crystals of pure ZnOTF tend to grow in a rhombus shape, with low orientation and low surface flatness. The surface flatness of OTF-M50 is greatly improved compared to pure ZnOTF. SO-M50 is similar to OTF-M50, with greatly improved surface flatness, and Zn is stacked in regular sheets.

[0072] Effect of MET on full battery performance and stability of vanadium-based cathode

[0073] Figure 4 The cycle life comparison chart of the KVO||Zn full battery assembled with the OTF-M10, OTF-M50, and OTF-M100 electrolytes of Example 3 and the OTF electrolyte of Comparative Example 1. The full battery of the OTF electrolyte decays rapidly, and the improvement of the OTF-M10 with only a small amount of MET added is very obvious. The OTF-M50 almost maintains 0 decay and stable cycle for more than 800 cycles, and the capacity retention rate of the battery after stabilization reaches an astonishing 99.8%. The OTF-M100 battery was also able to maintain a stable cycle for more than 300 cycles in the early stage.

[0074] Effect of MET on the cycling stability of Zn / / Zn symmetric batteries

[0075] Figure 5 Cycle life diagram of Zn||Zn symmetric battery assembled with OTF-M50 electrolyte of Example 4 and OTF electrolyte of Comparative Example 3, at 1 mA cm -2 / 1mAh cm -2 Under these conditions, the cycle stability of the Zn / / Zn symmetric battery assembled with OTF-M50 electrolyte is significantly improved compared with that of OTF without MET addition, and the cycle number of OTF-M50 is more than 800h.

[0076] Effect of MET additives on battery cycle performance

[0077] Figure 6 The cycle life diagram of the Zn||Cu symmetric battery assembled with the OTF-M50 electrolyte of Example 5 and the OTF electrolyte of Comparative Example 4. The OTF electrolyte experienced severe CE fluctuations and failure after a very short number of cycles. The cycle life and CE of the OTF-M50 half-cell with the addition of MET were significantly improved. The Zn||Cu half-cell of OTF-M50 was cycled for more than 2400 cycles with a coulombic efficiency of 100.9%. At 1mAcm -2 / 1mAh cm -2 and 5mA cm -2 / 1mAh cm -2 Under higher current density, only OTF-M50 can maintain a longer cycle life with a stable coulombic efficiency CE, and the average coulombic efficiency CE also reaches 100.89% and 100.4% respectively. MET can be adsorbed on the zinc negative electrode to effectively reshape and construct a stable Zn deposition environment, greatly improving the zinc plating / stripping stability in the electrolyte.

[0078] In summary, the bifunctional AZIBs additive provided in this application, methionine (MET), in terms of stabilizing the vanadium-based positive electrode, can promote the in-situ formation of a CEI film containing products such as ZnF2 on the surface of the vanadium-based positive electrode, thereby effectively inhibiting the dissolution and collapse of the vanadium-based positive electrode; on the other hand, MET participates in regulating the electronic state of the vanadium-based positive electrode surface and the Zn 2+ diffusion behavior, reducing the dissolution energy of the vanadium-based cathode and reducing the Zn 2+ The intercalation process destroys the structure of the vanadium-based cathode. Compared with the bare electrolyte, the K2V8O 21 ||Zn full battery at 1Ag -1 After 800 cycles at low current density, the capacity retention rate increased significantly from 10.2% to 99.8%.

[0079] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. Application of methionine as a bifunctional additive in aqueous zinc ion batteries.

2. The use according to claim 1, characterized in that: The aqueous zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte; The positive electrode includes a vanadium-based material and methionine; The negative electrode is a Zn negative electrode.

3. The use according to claim 2, characterized in that: The usage ratio of methionine to vanadium-based material is 1:1.5 to 1:

3.

4. The use according to claim 2, characterized in that: The vanadium-based material is selected from K2V8O 21 and / or V2O5.

5. The use according to claim 2, characterized in that: The electrolyte includes a zinc salt aqueous solution and methionine.

6. The use according to claim 5, characterized in that: In the electrolyte, the amount of methionine used is 0.01 mol / L to 0.1 mol / L.

7. The use according to claim 5, characterized in that: The zinc salt aqueous solution is selected from ZnOTF aqueous solution.

8. The use according to claim 2, characterized in that: The preparation method of the positive electrode comprises: mixing vanadium-based material and methionine in water, stirring evenly, and drying to obtain active material; mixing active material, acetylene black and PVDF to prepare slurry, coating the slurry evenly on graphite paper, and drying to obtain the positive electrode.

9. The use according to claim 5, characterized in that: The preparation method of the electrolyte comprises: adding methionine into a zinc salt aqueous solution.